Pediatric cervical Intravascular Papillary Endothelial hyperplasia (IPEH): A case report of an unusual presentation - Hussein Smaily, MD; Atilano lacson, MD, FRCPC; Dean Jeffery, MD, FRCPC; André Isaac, MD, MSc, FRCSC (Radiology Case Reports)
Intravascular Papillary Endothelial hyperplasia (IPEH) are benign vascular lesions rarely described in the pediatric population. We present here the case and the management of a 11-year-old child with a lateral neck mass. The diagnosis of IPEH can be challenging for the clinician and the radiologist as it may mimic other pathologic entities. The definite management consists of surgical excision and immune-histopathological examination to establish a diagnosis.